2021
DOI: 10.3390/cancers13040887
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation and Tumour-Infiltrating T-Cell Receptor Repertoire Diversity Are Predictive of Clinical Outcome in High-Grade B-Cell Lymphoma with MYC and BCL2 and/or BCL6 Rearrangements

Abstract: High-grade B-cell lymphoma, with MYC and BCL2 and/or BCL6 rearrangements (double/triple-hit high grade B-cell lymphoma, HGBL-DH/TH) constitutes a provisional entity among B-cell malignancies with an aggressive behavior and dire prognosis. While evidence for the essential prognostic role of the composition of the tumor-microenvironment (TME) in hematologic malignancies is growing, its prognostic impact in HGBL-DH/TH remains unknown. In this study, we outline the adaptive immune response in a cohort of 47 HGBL-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Accordingly, our findings in the TRB repertoire of the CD8-predominant AITL TME may be interpreted by TME immunosuppression. Additionally, in keeping with knowledge from other tumors ( 13 , 32 ), the narrowed TR and IGH repertoires in the TME of CD8-predominant AITL may indicate downregulated anti-tumor immunity via inadequate immunosurveillance of tumor T-cell neoantigens.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Accordingly, our findings in the TRB repertoire of the CD8-predominant AITL TME may be interpreted by TME immunosuppression. Additionally, in keeping with knowledge from other tumors ( 13 , 32 ), the narrowed TR and IGH repertoires in the TME of CD8-predominant AITL may indicate downregulated anti-tumor immunity via inadequate immunosurveillance of tumor T-cell neoantigens.…”
Section: Discussionmentioning
confidence: 67%
“…TIL subsets and proportions directly reflected TME immune function and have been shown to be predictive of various malignancies ( 17 19 ). TR and IGH repertoires of TME dictate TIL-T and TIL-B variety and represent the ability to identify tumor antigens and combat tumor immunoevasion ( 13 , 14 ). Furthermore, gene expression profiling may reveal immunological activity by examining the regulation of related pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In melanoma, breast and colon cancer, expanded Tcell clones are associated with response to immunotherapy treatment (77)(78)(79). In BCL, a restricted TR repertoire is found to be associated with poor outcome in DLBCL treated without immune-checkpoint inhibition (80) and in high grade B-cell lymphomas (81). Obviously, more studies are needed for different lymphoma types and treatments to understand the full potential of TR repertoire analysis in BCL.…”
Section: Tr Repertoire Analysis In Patients With Solid Tumors and Lym...mentioning
confidence: 99%
“…The cut-off values of Ki-67 for optimal risk stratification are discussed conversely [ 29 , 30 , 31 ]. Among a large spectrum of solid tumors and hematological malignancies, it has been shown that the Glasgow Prognostic Score (GPS) reflects a representative and handy tool to identify cancer patients at risk for both early progression and all-cause mortality [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. GPS examines two essential mechanisms of tumor growth, progression and aggressiveness.…”
Section: Introductionmentioning
confidence: 99%